The hitchhiker's guide to parasite dissemination. (8th July 2019) - Drewry, Lisa L.; Sibley, L. David
Abstract: Toxoplasma gondii ( T. gondii ) is a parasitic protist that can infect nearly all nucleated cell types and tissues of warm‐blooded vertebrate hosts. T. gondii utilises a unique form of gliding motility to cross cellular barriers, enter tissues, and penetrate host cells, thus enhancing spread within an infected host. However, T. gondii also disseminates by hijacking the migratory abilities of infected leukocytes. Traditionally, this process has been viewed as a route to cross biological barriers such as the blood–brain barrier. Here, we review recent findings that challenge this view by showing that infection of monocytes downregulates the program of transendothelial migration. Instead, infection by T. gondii enhances Rho‐dependent interstitial migration of monocytes and macrophages, which enhances dissemination within tissues. Collectively, the available evidence indicates that T. gondii parasites use multiple means to disseminate within the host, including enhanced motility in tissues and translocation across biological barriers.